Teknik Pernapasan Buteyko dan Arus Puncak Ekspirasi pada Pasien Asma - I Kadek Ananta Wijaya; I Made Mertha; I Gusti Ayu Ari Rasdini (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2020)
Asthma is a chronic inflammatory disorder in the airway. The peak expiratory flow rate is one of the human lung function tests used to assess the ability of lung function and provide an image of the airway disorder. This study aims to determine the effect of Buteyko’s respiratory technique on peak expiratory flow rate in asthma patients. The type of research is Pre-Experimental Design with One-Group Pretest-Posttest using purposive sampling. The sample size is 22 people. The patient's peak expiratory flow rate is measured using a peak flow meter. The results of peak expiratory flow rate of the patient tested using paired t- test. The results showed that the peak expiratory flow rate prior to Buteyko’s respiratory technique of 75.764%, and after given breathing Buteyko's breathing techniques, peak expiratory flow rate of patients showed an increase to equal to 79.986%. Based on the results of the research, the value of ρ-value = 0.000 alpha (0,05), it can be concluded that there is influence of giving respiratory technique Buteyko can increase the peak expiratory flow rate in asthma patient. It is expected that the hospital to consider implementing Buteyko's breathing techniques for asthma patients.